Analisis Pengetahuan Remaja Putri Mengenai Anemia Sebelum dan Sesudah Penyuluhan - Safitri, Yunni (Jurnal Kebidanan Malakbi, 2022)
The nutritional problem of adolescents in Southeast Asia is anemia, which is 25-40% of adolescent girls experiencing mild to severe levels of anemia. Lack of knowledge about it causes young women to be anemic because nutrition is essential for growth and development. The study aims to know the difference in young women's knowledge of anemia before and after counseling. This type of research is a quantitative with a descriptive design. The study was conducted at a new high school on November 15, 2021. The study population was an x-class young woman of 248 with a sample number of 71. Sampling techniques using random stratified sampling. Research instruments use questionnaires assessed from pretest and posttest results. The treatment of anemia started before the posttest. Young women knowledge before good counseling 54 people (76%) and after the good advice of 70 people (99%). Young women knowledge covers the understanding of anemia before good practice 43 (61%) and after the good practice of 67 people (94%), the knowledge that causes anemia before counseling enough 30 people (42%) and after the good practice of 58 (82%), the knowledge of the signs and symptoms of anemia before the good 52 (73%) and after the good enlightenment of 60 (85%), Knowledge of the impact of anemia before counseling is just 38 people (54%) and after the good 46 (65%) and the knowledge of the initial treatment of anemia before the good at 67 (94%) and after the good at 70 (99%). There is an increase in young women's knowledge of anemia after counseling. It is best for educational institutions to improve health education especially on anemia in young women by facilitating school vessels such as the formation of pik KRR or other vessels that could answer students' questions about anemia and counseling.